Programa Diadema Mais Educação: uma experiência de educação integral e proteção integral - Sanches, Ana Lucia (2017)
The thesis describes the interconnection between integral education and social protection, traversing the meanings of the Integral term, based on the Freirean view and the legal framework of childhood policies, especially the ECA. The locus of the research is the city of Diadema, recognized for its long tradition of social participation and its social scene, characterized by high demographic density and disordered occupation of the soil. The objective of the research is Diadema’s More Education Program, an Integral Education program developed between 2009 and 2012, based on the federal program More Education and faceted by the city council that brought together political consensus, and provided a political architecture that integrated different subjects in the sphere of strategic management and operational management, based on social participation and occupation of city territories. The general objective of the research is: To analyze the experience of the Diadema More Education Program between 2009 and 2012, in the relation of full-time education and social protection, and the specific objectives are: To establish a relation between dimensions of Integral in the curriculum, from the Freirean reading; To analyze the relation of the Integral concept to the dimensions of social protection; Identify in the experience of Diadema, between 2009 and 2012, the multiple dimensions of Integral Education the implementation of a program of Integral Education in Full-Time. The nature of the research is qualitative, based on a bibliographical survey in the areas of Education and Curriculum, Social Service and Social Sciences and documentary research in the public documents of the Municipal Secretary and especially in the document "The integration of the school with the city by the ways of integral education" where are collected the testimonies of school directors, of coordinating bodies, the community education officers, family members and partner organizations. The thesis is divided into three sections, in which it is presented from the Freirean matrix, the concepts of Integral Education and social Protection, revealing the importance of the expansion of time for the childhood of the peripheries; the importance of the Lula and Dilma governments to include the Integral education agenda, the organization of the Diadema More Education Program, its management structure, curriculum design and training, routine, territories and subjects of the Program, and the analysis of the testimonies of the subjects of Integral Education in Diadema, and its reflexes in the effective intersection between Social Protection and Integral Education, and, as a dismemberment of this action, the guarantee of a curriculum that makes effective the rights of children, present in the legal framework. The research reveals that the experience of Diadema reflects the advances of a public policy for childhood, and points to a new format of the school, recognized from the formative process and corroborates with the fair living of the children of the periphery, which composes access to social goods and local knowledge